Improvement of gamete quality and its short-term storage: an approach for biotechnology in laboratory fish - Yasui, George Shigueki; Senhorini, José Augusto; Shimoda, Eduardo; Pereira-Santos, Matheus [UNESP]; Nakaghi, Laura Satiko Okada [UNESP]; Fujimoto, Takafumi; Arias-Rodriguez, Lenin; Silva, Luciano Andrade (Cambridge Univ Press, 2015)
In fish, in vitro fertilization is an important reproductive tool used as first step for application of others biotechniques as chromosome and embryo manipulation. In this study, we aimed to optimize gamete quality and their short-term storage from the yellowtail tetra Astyanax altiparanae, for future application in laboratory studies. Working with sperm, we evaluated the effects of spawning inducers (carp pituitary gland and Ovopel (R) [(D-Ala6, Pro9-NEt) - mGnRH+metoclopramide]) and the presence of female on sperm motility. Additionally, we developed new procedures for short-term storage of sperm and oocytes. Briefly, sperm motility was higher when male fish were treated with carp pituitary gland (73.1 +/- 4.0%) or Ovopel (R) (79.5 +/- 5.5%) when compared with the control group treated with 0.9% NaCl (55.6 +/- 27.2%; P=0.1598). Maintenance of male fish with an ovulating female fish also improved sperm motility (74.4 +/- 7.4%) when compared with untreated male fish (42.1 +/- 26.1%; P=0.0018). Storage of sperm was optimized in modified Ringer solution, in which the sperm was kept motile for 18 days at 2.5 degrees C. The addition of antibiotics or oxygen decreased sperm motility, but partial change of supernatant and the combination of those conditions improve storage ability of sperm. Fertilization ability of oocytes decreased significantly after storage for 30, 60 90 and 120 min at 5, 10, 15 and 20 degrees C when compared with fresh oocytes (P=0.0471), but considering only the stored samples, the optimum temperature was 15 degrees C. Those data describe new approaches to improve semen quality and gametes short-term storage in yellowtail tetra A. altiparanae and open new possibilities in vitro fertilization.
Keywords: Cryopreservation; Sperm; Oocyte; Fish; Yellowtail tetra